2019
DOI: 10.7717/peerj.7235
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomics of human pathogenic parasiteLeishmania(Viannia)panamensis

Abstract: Background The human parasite Leishmania (V.) panamensis is one of the pathogenic species responsible for cutaneous leishmaniasis in Central and South America. Despite its importance in molecular parasitology, its mitochondrial genome, divided into minicircles and maxicircles, haven’t been described so far. Methods Using NGS-based sequencing (454 and ILLUMINA), and combining de novo genome assembly and mapping strategies, we report the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Here we present the sequences of 17 new full trypanosomatid maxicircles. The big problem of maxicircle sequencing is the divergent region, which remains difficult to assemble even using the modern NGS techniques [31,32]. In the current work we used PacBio datasets to assemble maxicircles, but even with this technique the assemblies often suffered from the low coverage in their DR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we present the sequences of 17 new full trypanosomatid maxicircles. The big problem of maxicircle sequencing is the divergent region, which remains difficult to assemble even using the modern NGS techniques [31,32]. In the current work we used PacBio datasets to assemble maxicircles, but even with this technique the assemblies often suffered from the low coverage in their DR.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sequencing technologies some maxicircles were sequenced completely [12,[30][31][32]. However, even paired-end Illumina sequencing was often not sufficient to assemble the complete maxicircle, and, because of that, most studies were focused only on coding region with short flanks [11,13,18], and even the most recent assembly from Illumina data had recovered only 3.5 kb of DR (as in [32]). Analysis of 3.5-kb and 5-kb regions of DR of Trypanosoma lewisi, flanking 12S and ND5 genes, respectively, revealed that these loci have different patterns of repeats [31].…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, until very recently, the mitochondrial genomes of Leishmania parasites have been neglected in the gold era of nuclear genome sequencing. In the field, a few works, in which NGS technologies are used to determine Leishmania mitochondrial genomes, have been published [5,54,59]. In these studies, either previous kDNA purification [5] or selective PCR-amplification of maxicircles [54] steps were included.…”
Section: Discussionmentioning
confidence: 99%
“…have 35 to 36 chromosomes in their nuclear genomes [ 35 , 36 ], and it is characterized by both mini and maxi circles kinetoplast DNA structures [ 37 ]. Various chromosomal and kinetoplast DNA sequences have been evaluated as targets for diagnostic systems and the extra-chromosomal circles showed always the best sensitivity and represent currently the most employed target with worldwide diffusion [ 38 , 39 ]. The use of high-copy 18S and minicircle kDNA sequences as a target usually allows amplification at the genus or subgenus level, due to their conserved sequences or to the heterogeneity of minicircle classes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%